High-Throughput Mapping of B Cell Receptor Sequences to Antigen Specificity - Setliff, Ian; Shiakolas, Andrea R.; Pilewski, Kelsey A.; Murji, Amyn A.; Mapengo, Rutendo E.; Janowska, Katarzyna; Richardson, Simone; Oosthuysen, Charissa; Raju, Nagarajan; Ronsard, Larance; Kanekiyo, Masaru; Qin, Juliana S.; et al. (Cell, 2019)
B cell receptor (BCR) sequencing is a powerful tool for interrogating immune responses to infection and vaccination, but it provides limited information about the antigen specificity of the sequenced BCRs. Here, we present LIBRA-seq (linking B cell receptor to antigen specificity through sequencing), a technology for high-throughput mapping of paired heavy- and light-chain BCR sequences to their cognate antigen specificities. B cells are mixed with a panel of DNA-barcoded antigens so that both the antigen barcode(s) and BCR sequence are recovered via single-cell next-generation sequencing. Using LIBRA-seq, we mapped the antigen specificity of thousands of B cells from two HIV-infected subjects. The predicted specificities were confirmed for a number of HIV- and influenza-specific antibodies, including known and novel broadly neutralizing antibodies. LIBRA-seq will be an integral tool for antibody discovery and vaccine development efforts against a wide range of antigen targets. [Display omitted] •LIBRA-seq: high-throughput mapping of BCR sequence to antigen specificity•Identified HIV- and influenza-specific B cells in two HIV-infected subjects•Predicted antigen reactivity for thousands of single B cells•Identified a previously unknown broadly neutralizing HIV antibody LIBRA-seq enables high-throughput mapping of B cell receptor sequence to antigen specificity at the single-cell level.